Faidatus; THE PERCEPTION OF STUDENT ABOUT JAPANESE EDUCATION TRAINEE TEACHING SKILL - Faidatus Tsalis; Ai Sumirah Setiawati; Andy Moorad Oesman (Chi'e: Journal of Japanese Learning and Teaching, 2017)
Abstract In teaching practice process, a trainee should be able to interact with students well. Students are important element in learning process. Based on the preliminary results of the study by spreading questionnaire to the students, it was known that there was positive assessment and and negative assessment about the trainee. This study attempts to know the perception of students about trainee’s teaching skill. The sample was 10% of total students that were ever taught by the trainee in SMA N 1 Ungaran, SMA N 1 Salatiga, SMA N 5 magelang, SMA N 9 Semarang and SMA N 1 kendal. The data collection technique used the questionnaire. In this study, the result of the data was analyzed by using descriptive technique percentage. Based on the study result, the perception of students about trainee’s teaching skill in Department of Japanese Education at Semarang State University was high category (69,24%). Abstrak Pada proses pembelajaran ketika Praktik Pengalaman Lapangan berlangsung, mahasiswa praktikan harus mampu berinteraksi baik dengan siswa. Siswa merupakan unsur penting dalam proses pembelajaran. Berdasarkan hasil studi pendahuluan dengan menyebarkan angket kepada siswa, diketahui bahwa ada penilaian positif dan ada pula penilaian negatif mengenai mahasiswa praktikan. Penelitian ini bertujuan untuk mengetahui bagaimana persepsi siswa mengenai keterampilan mengajar mahasiswa praktikan. Sampel penelitian ini adalah 10% dari total siswa yang pernah diajar oleh mahasiswa praktikan di SMA N 1 Ungaran, SMA N 1 Salatiga, SMA N 5 magelang, SMA N 9 Semarang dan SMA N 1 kendal. Teknik pengumpulan data menggunakan angket. Hasil data yang diperoleh dianalisis dengan teknik deskriptif persentase. Berdasarkan hasil penelitian, diketahui bahwa persepsi siswa mengenai keterampilan mengajar mahasiswa praktikan Prodi Pendidikan Bahasa Jepang Unnes secara keseluruhan berada pada kategori tinggi (69,24%).